1974
DOI: 10.1177/00220345740530062001
|View full text |Cite
|
Sign up to set email alerts
|

Reactions in Glass Ionomer Cements: II. An Infrared Spectroscopic Study

Abstract: The transmission and attentuated total reflectance spectra of a dental cement formed from an aluminosilicate glass and aqueous polyacrylic acid (ASPA) are reported. Interpretation of spectra show that a siliceous hydrogel is formed together with the polyacrylate salts of calcium and aluminum. In the fully hardened cement a minor proportion of -COOH remains unconverted to -COO-groups for steric reasons. Chemical studies on the formation of the glass-ionomer cement, ASPA, show that the setting mechanism can be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(44 citation statements)
references
References 6 publications
0
43
0
1
Order By: Relevance
“…Also in the region of 1540-1630cm [39] , indicating that in this case both Ca 2+ and Sr 2+ are the prominent crosslinking ions during the setting reaction. Previous studies by Nicholson et al reported Ca-PAA complexes in the region of 1550cm -1 when studying the effect of (+)-tartaric acid on GPCs [28] , and earlier studies by Crisp et al also found Ca-PAA complexes in the region of 1560cm -1 [40] . It is also evident that there is no shift in wavenumber over time suggesting that the cements have a final set within 24 hours, which agrees with mechanical properties.…”
Section: Resultsmentioning
confidence: 86%
“…Also in the region of 1540-1630cm [39] , indicating that in this case both Ca 2+ and Sr 2+ are the prominent crosslinking ions during the setting reaction. Previous studies by Nicholson et al reported Ca-PAA complexes in the region of 1550cm -1 when studying the effect of (+)-tartaric acid on GPCs [28] , and earlier studies by Crisp et al also found Ca-PAA complexes in the region of 1560cm -1 [40] . It is also evident that there is no shift in wavenumber over time suggesting that the cements have a final set within 24 hours, which agrees with mechanical properties.…”
Section: Resultsmentioning
confidence: 86%
“…6 Although the ability of a material to set in the dark can be used as a test to determine the occurrence of an acid-base reaction, such a test cannot be conclusive in the presence of chemical initiators. 15 Previous FT-IR studies of glass ionomer cements have been performed using attenuated total reflectance spectroscopy (ATR) 7,8 or micro FTIR experiments. 9 The ATR experiments have mainly been employed for short-term studies of complex formation in conventional glass ionomer cements, and would be less suitable for longer-term studies, because dehydration of the cement would inevitably occur if the cement remained in dry conditions for a long period of time.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable debate and controversy over various aspects of the setting reaction, including whether the setting reaction continues with time and how both the silica gel phase and polysalt phase affect the long term mechanical properties [5][6][7].…”
Section: Introductionmentioning
confidence: 99%